2009
DOI: 10.1111/j.1365-2184.2008.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of Notch signalling in the regeneration of rat tracheal epithelium

Abstract: During tracheal epithelial regeneration, Notch signalling maintains an undifferentiated state and promotes proliferation among a population of tracheal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144). It is also known that Notch1 plays a major role in the control of the adaptive response of the heart to stress conditions (139) and is activated during liver regeneration (141), further confirming a possible involvement of the Notch pathway in pathomechasim of lung fibrosis.…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosissupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144). It is also known that Notch1 plays a major role in the control of the adaptive response of the heart to stress conditions (139) and is activated during liver regeneration (141), further confirming a possible involvement of the Notch pathway in pathomechasim of lung fibrosis.…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosissupporting
confidence: 86%
“…During the injury a similar situation was observed in NICD3 localization of rat tracheal epithelial cells. It was suggested that Notch activation plays a role in the maintenance of an undifferentiated state of epithelial cells and the promotion of proliferation of cells (144). We suggest that NICD1 may have an impact on AECII transdifferentiation in AECI.…”
Section: Alveolar Epithelium As a Target Cell Type For Notch Signalingmentioning
confidence: 67%
“…The rationale for examining the Notch pathway in renal regeneration includes the role this pathway plays in the regenerative response to injury in adult tissues such as kidney, liver, bone marrow, skin, muscle, intestine, heart, trachea, and pancreas (1,16,17,24,30,31,36,42,48,54). In addition, Notch signaling is involved in self-renewal and cell-fate commitment of tissue stem cells (14,21).…”
mentioning
confidence: 99%
“…It has been reported that NOTCH1, another molecule in Notch family members, expression is associated with cell aggressiveness and 5-FU drug resistance in human esophageal squamous cell carcinoma cell lines in vitro, and also with poor survival in human esophageal squamous cell carcinomas (19). It has also been reported that expression levels of Notch3 were increased in rat tracheal epithelial cells after treatment with 5-FU (20). NOTCH3 knockdown enhanced the sensitivity of nasopharyngeal carcinoma cells to CDDP treatment (21), and NOTCH3 overexpression correlated with shorter progressionfree/overall survival in patients with advanced stage ovarian carcinoma treated with platinum and taxane (22).…”
Section: Discussionmentioning
confidence: 82%